MANFAAT KANOPI POHON DALAM UPAYA PENYIMPANAN DAN DAYA SERAP KARBON DI KAWASAN PERUMAHAN - Lukmanniah, Purwanti; Fatimah, Indung Sitti (Jurnal Lanskap Indonesia, 2016)
Residential development in urban areas was requiring extensive landscape changes. This development caused the decreases of urban green land. The high rate of CO2 in the atmosphere is one impact of the reduction of green land in urban area.The existing plants are unable to sequester the amount of CO2 in atmosphere. Plans especially trees are landscape elements which can reduce CO2 in the atmosphere through the photosynthesis process. With this research we can see and know how large the benefits of tree for carbon storage and sequestration in residential. This research was held in two residential that Bukit Cimanggu City and Yasmin, Tanah Sareal, Bogor. Analysis was done to spatial data using ArcView and CITYgreen5.4 extension. This report showed that the greater of trees canopy and trees number then the greater of the amount of carbon storage and sequestration. The result of this research are tabular data and spatial data with simulations examples of open green space (trees) from analysis area in each residential.